Political Identity in the Narratives of April 9, 1948 in Boyacá - Bohórquez Aunta, Camila Andrea; González González, Erika Liliana; Torres Sanmiguel, Alexander (Universidad Pedagógica y Tecnológica de Colombia, 2020)
The purpose of this article is to analyze how political identity affects the construction of the narratives of April 9, 1948 in Boyacá. It is framed under the historical-hermeneutic paradigm, the qualitative approach and the sociolinguistic model oriented in the analysis of testimony. The field work was carried out based on semi-structured interviews that build a corpus of 23 stories of 16 witnesses from Boavita, Cómbita and Tunja. The results are focused on understanding the influence of the speaker's political identity on the narration of past events.